Variations in body condition score, inflammatory and metabolic biomarkers predict cognitive changes in clinically healthy senior cats - Memoli, Holly; Albertini, Mariangela; Grader, Irit; Provoost, Lena; Filipe, Joel; Piotti, Patrizia; Scarpa, Paola; Stefanovski, Darko; Pirrone, Federica; Siracusa, Carlo (Frontiers in Aging Neuroscience, 2025)
ObjectivesThe present study aimed to identify immune, metabolic, and hematological biomarkers, among those commonly monitored in clinical practice, that are predictive of age-related behavioral and cognitive changes in clinically healthy elderly cats, with the objective of highlighting potential patterns of inflammaging.MethodsA cross-sectional observational study was conducted at two veterinary institutions and involved 90 clinically healthy, privately owned domestic cats aged 7–16 years. All cats underwent physical examinations, laboratory, and behavioral screenings. Serum concentrations of the pro-inflammatory cytokine interleukin-1beta (IL-1β) and the anti-inflammatory cytokine IL-10 were measured using ELISA as markers of peripheral inflammation. Behavioral and cognitive changes were assessed using the Feline Behavioral Assessment and Research Questionnaire and Feline Cognitive Dysfunction Rating Chart, respectively. Multivariate regression analysis was used to assess the association between behavioral and cognitive outcomes and immune, metabolic, and biochemical predictors (p < 0.05).ResultsSignificant associations were identified between immune, hematological, and metabolic phenotypes indicative of chronic inflammation and cognitive changes assessed using the FCDRS Sleep–wake cycle disturbances were strongly and positively predicted by increased body condition score (BCS), alanine aminotransferase (ALT), creatinine, white blood cells (WBCs), globulin, and IL-1β levels, and negatively predicted by albumin and neutrophils. Anxiety was positively associated with higher BCS, creatinine, and IL-10, and negatively associated with IL-1β. Activity levels were positively predicted by IL-10. Altered social interactions and house-soiling were significantly associated with increased BCS.Conclusion and relevanceFindings suggest that changes in physiological parameters describing patterns of chronic inflammation are associated with measurable cognitive changes in aging cats, in the absence of overt clinical disease, which is consistent with the concept of inflammaging. Routine monitoring of standard bloodwork and BCS may offer an accessible means of tracking chronic subclinical inflammation and predicting cognitive aging in senior feline patients. These results highlight the importance of proactive cognitive screening and client education to preserve welfare and the human-animal bond in aging cats.